INTERACTIVE LEARNING MEDIA FOR DYSLEXIC STUDENTS OF ELEMENTARY SCHOOL - Tita Rosita; Tuti Alawiyah; Endang Rochyadi; Sunardi Sunardi (IKIP Siliwangi, 2020)
The purpose of this study is to develop web-based learning media to improve reading comprehension of dyslexic students. Dyslexia is a condition caused by neurobiological abnormalities that are characterized by difficulty in recognizing words accurately in spelling and inability to encode symbols which lead to reading disorder. The research method used is research and development. This research develops web-based learning media called LexiRoom learning applications. The LexiRoom web was trialed to dyslexic students of the fourth grade of elementary school and obtained effective results to help students to have better comprehension of words and sentences within a paragraph.